Bangladesh in Anglophone and vernacular literature : cultural imaginings of a postcolonial nation - Iqbal, Asif (Professor of English); Iqbal, Asif (Professor of English) (Routledge research on Asian literature, 2026)
"This book illuminates individual and collective imaginings of postcolonial Bangladesh. It explores the emergence of Bangladesh as a nation from a variety of perspectives. The author studies the impact of Muslim nationalism on the subaltern life-worlds of East Bengal during the Partition, religious minorities and their insecurity in East Pakistan, East Pakistan's political insurgencies, the victims of the 1971 Bangladesh Liberation War, the Indian stake in the 1971 War and the cosmopolitan interpretations of the war. The literary and cultural texts that inform this project include contemporary Bengali novels, South Asian Anglophone literature, as well as selected visual media and digital sources. The project's reading of these texts in conjunction with politics and history has interdisciplinary relevance. This book will be of interest to researchers in South Asian Literature, South Asian History and Culture, World Literatures in English as well as Area Studies, Security Studies, and Political Theory"-- Provided by publisher.